-2x-(5+4x)+4=

Simple and best practice solution for -2x-(5+4x)+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-(5+4x)+4= equation:


Simplifying
-2x + -1(5 + 4x) + 4 = 0
-2x + (5 * -1 + 4x * -1) + 4 = 0
-2x + (-5 + -4x) + 4 = 0

Reorder the terms:
-5 + 4 + -2x + -4x = 0

Combine like terms: -5 + 4 = -1
-1 + -2x + -4x = 0

Combine like terms: -2x + -4x = -6x
-1 + -6x = 0

Solving
-1 + -6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -6x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -6x = 0 + 1
-6x = 0 + 1

Combine like terms: 0 + 1 = 1
-6x = 1

Divide each side by '-6'.
x = -0.1666666667

Simplifying
x = -0.1666666667

See similar equations:

| 300x-0.36=800x+0.74 | | (-2x)-5+4x+4= | | 4(x-7.6)=1.6 | | 4x^2-20x=8 | | x-8=2.82 | | 3x^3-6x^2-x+5=0 | | 4x^4+6x^2+x+5=0 | | -2x-5+4x+4= | | 5s=2s+15 | | 3x^3+6x^2+x=-5 | | 24x+31x=21 | | 14p-10=8+p | | 8x^4+4x^3+2x^2+x=0 | | 3x^3+6x^2+5=0 | | 2b+4(5+4b)=56 | | 3x^3+6x^2+x+5=0 | | X^2-5X-6=2-3X | | -2(5a-4)+3=61 | | N(t)=20t-t^2 | | 2(2+5m)=54 | | 3-5f=12 | | 3(1+4r)=-57 | | -3(4x-1)+3=66 | | (8.7+0.4)(3.6-0.1)= | | 7n+7+6n=16+n-3+6n | | (9-3i)+(-9+3i)= | | 5-8e=7 | | -2x-1=-11+8x-5x | | (0.5)(0.5)-0.2= | | (5-7i)(2+4i)= | | x=46-14 | | -3b-3+3b+16=1-2b |

Equations solver categories